Avaliação dos custos da IATF e TETF na produção de bezerros PO da raça Nelore - (:unkn) unknown (Universidade Brasil, 2024)
Reproductive efficiency is fundamental for high genetic beef cattle herds and not always quickly, capital turnover achieved. The literature is scarce about evaluation of finance information in terms of high genetic calf production. This evaluation is important, considering the high value in capital invested. The present study evaluated two reproductive biotechnologies TAI (timed artificial insemination ) and FTET (fixed timed embryo transfer), considering costs, losses and profits of activities in two retreat farm which are from the same property in Comodoro, Mato Grosso, during the breeding season of 2022 to 2023. At Retreat 1, 432 Nelore pure bred beef cattle were submitted to TAI protocols, while at Retreat 2, 375 half blood Nelore cattle were used as recipient cattle for FTET. The embryos transferred were from in vitro production laboratory, being IVF (in vitro fertilized) embryos processed for storage based on distinct methodologies: fresh, vitrified and DT (direct transferred). The TAI resulted in 311 pregnant cattle, representing 72% of pregnancy rates, R$ 228.200,00; total costs and R$ 733,76 cost for pregnancy; while FTET resulted in 243 pregnant recipient, with 65% of pregnancy rates, with R$ 287.787,00, total costs and R$ 1.183,48 cost for pregnancy. Regarding the Nelore pure bred calf production costs, the numbers and costs were respectively TAI (n= 276) and R$ 826,81; while for FTET (n= 175), the costs were R$ 1.644,50. FTET exceeded TAI in R$ 59.587,00; considering high pregnancy losses for this biotechnology until birth of calves , which represented 28% of FTET lost rate, resulting in additional 11% of losses compared to TAI (17%) lost rate. FTET have currently being implanted, nevertheless, measures and criteria needed to be adjusted, as nutrition and reproductive management; all those aspects searching for sanitary control, which would certainly minimize the findings reported unitl the present moment.
Keywords: Biotecnologia; Embrião; Financeiro; Reprodução; Vacas; Produção Animal